Evaluating the sustainability of Vilnius city residential areas - Viteikienė, Milda; Zavadskas, Edmundas Kazimieras (Journal of Civil Engineering and Management, 2007)
The objective of this article is to propose a methodology that would enable to rank residential areas according to the indices of sustainable development and to establish the rank of their priorities. The task was framed basing on the survey performed by RAIT (Market analysis and group of survey) for evaluation of the most desirable residential area in Vilnius city. Vilnius residents took part in this survey. Only Vilnius city residential areas and their characteristic indices were sorted out from the survey performed by RAIT. A system of 22 indices defining the sustainability aspects was compiled. Residential areas were evaluated for their facilities, residential and business environment. On the basis of the surveys performed by experts, the significances of indices were determined. Application of multipurpose evaluation method COPRAS (Complex Proportional Assessment) led to establishment of the rank of priorities of residential areas in respect of their sustainability.Vilniaus miesto gyvenamųjų rajonų darnos vertinimasSantrauka. Straipsnio tikslas – pasiūlyti metodiką, kaip surikiuoti gyvenamuosius rajonus pagal darnios plėtros rodiklius ir sudaryti jų prioritetų eilutę. Suformuluotas uždavinys remiantis Vilniaus miesto RAIT atlikta apklausa patraukliausiam rajonui įvertinti. Šioje apklausoje dalyvavo Vilniaus miesto gyventojai. Iš apklausos buvo atrinkti tik Vilniaus miesto gyvenamieji rajonai (mikrorajonai) ir juos apibūdinantys rodikliai. Buvo sudaryta 22 rodiklių sistema, charakterizuojanti darnos aspektus. Gyvenamieji rajonai vertinami pagal infrastruktūrą, gyvenamąją bei verslo aplinką. Remiantis ekspertų apklausomis, nustatyta rodiklių reikšmė. Taikant daugiatikslio vertinimo metodą COPRAS (Complex Proportional Assessment), sudaryta gyvenamųjų rajonų pagal jų darną prioritetų eilutė.Reikšminiai žodžiai: darnus vystymasis, miesto gyvenamieji rajonai, COPRAS, vertinimas.First Published Online: 14 Oct 2010